Introduction to physical education, exercise science, and sport studies - Lumpkin, Angela (McGraw-Hill, 2002)
This accessible introductory text explores the history, philosophies, and principles of today's physical education programs within a practical, career-oriented framework. The text explores the wide variety of career opportunities available, and includes a greater focus on non-teaching related careers in physical education and sport